Bullying and malocclusion in adolescence: a case report - Grassia, Vincenzo; Rotolo, Rossana Patricia; Nucci, Ludovica; d'Apuzzo, Fabrizia; Perillo, Letizia (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Adolescents with bad malocclusion can more often be victims of bullying and the improvement of their facial appearance through oral rehabilitation is nowadays an important issue. The aim of this case report was to describe the orthodontic treatment in a teenager with a dentoskeletal malocclusion exposed to bullying to correct his occlusal problems and improve facial esthetics and quality of life. The patient, a boy aged 13.5 years, had a class II, division 1, malocclusion with hyperdivergent pattern, mandibular asymmetry, constricted maxillary arch and molar crossbite, increased overjet, lower mild crowding and lip sucking. A two-phase approach was necessary to achieve proper occlusion, better esthetics and promote the patient’s self-esteem with consequent greater serenity of his family.